Faktor-Faktor Penentu Perdagangan Biji Pala Indonesia - Lina Samhina; Rita Nurmalina; Netti Tinaprilla (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2023)
The export value of the whole nutmeg and nutmeg powder has increased yearly. Nevertheless, Indonesia's dependence on imports of nutmeg is high. This condition illustrates that Indonesia has not optimally utilized its export opportunities. Optimizing export opportunities can be done by paying attention to the factors that affect exports. Researchers used secondary data on the whole and nutmeg powder from 2012 to 2019 with research variables: Indonesia's GDP, GDP of export destination countries, economic distance, population, and sanitary and phytosanitary (SPS) dummy. The processes of data use a gravity model approach. The results showed that the GDP of both countries and the SPS had a negative effect on trade in the whole nutmeg, while economic distance and population had a positive impact. Meanwhile, the effect on trade in nutmeg powder by Indonesia's GDP, GDP of export destination countries, and the population is positive, economic distance is negative, and the SPS has an insignificant effect. The policy implication is the government and stakeholders should choose trading partners with large populations and make post-harvest handling rules to minimize the impact of SPS barriers. Meanwhile, to increase the trade in nutmeg powder, choosing a trading partner with a high GDP is necessary.